Toward a goal-oriented view of customer journeys - Larissa Becker; Elina Jaakkola; Aino Halinen (Emerald, 2022)
Purpose: Customer experience research predominantly anchors the customer journey on a specific offering, implying an inherently firm-centric perspective. Attending calls for a more customer-centric approach, this study aims to develop a goal-oriented view of customer journeys.
Design/methodology/approach: This study interprets the results of a phenomenological study of a transformative journey toward a sober life with the self-regulation model of behavior to advance understanding of customer journeys.
Findings: The consumer’s journey toward a higher-order goal encompasses various customer journeys toward subordinate goals, through which consumers engage in iterative cognitive and behavioral processes to adjust or maintain their experienced situation vis-à-vis the goal. Experiences drive behavior toward the goal. It follows that negative experiences may contribute to goal attainment.
Research limitations/implications: This study highlights the importance of looking at the consumers’ higher-order goals to obtain a more holistic understanding of the customer journey. Practical implications: Companies and organizations should extend their view beyond the immediate goals of their customers to identify relevant touchpoints and other customer journeys that affect customer experience.
Originality/value: This study proposes a conceptualization of the customer journey, comprising goal-oriented processes at different hierarchical levels, and it demonstrates how positive and negative customer experiences spur behaviors toward the higher-order consumer goal. This conceptualization enables a more customer-centric perspective on journeys.